The Role of English Language Textbooks in Environmental Education - Benchekroune, Lamiae; Touaf, Larbi (International Journal of Language and Literary Studies, 2025)
Many people tend to limit the function of language textbooks to the teaching of language skills and language components (i.e., reading, listening, speaking, writing, grammar, and vocabulary). By contrast to the former point of view, this paper argues that the role of language textbooks far exceeds the classical mission of teaching language per se. In fact, we think that language textbooks have a social responsibility too. Language textbooks need to teach students about different aspects of civic education, including environmental education (EE). Also, we believe in the potential of all language textbooks (English, Amazigh, Arabic, French, Spanish language textbooks, etc.) in promoting EE, with a particular focus on English language teaching (ELT) textbooks for this paper. So, in theory, we defend the capability of language textbooks in addressing environmental concerns. Unfortunately, in practice, former textbook analyses reflect that the vast majority of textbook evaluators are not satisfied with the anthropocentric results they end up finding. As a result, we choose to react to the dissatisfaction of textbook evaluators and to contribute to the discussion by proposing an alternative interpretation on how the anthropocentric results can be viewed otherwise, especially in a way that makes them look more useful and more valuable.